Indicadores do patenteamento de materiais armazenadores de hidrogênio voltados para o monitoramento tecnológico - Oviedo Díaz, Sergio Manuel (2016)
Hydrogen is considered the energy carrier of the future, due to its high energy content and the possibility of its sustainable production. However, its broader implementation depends on overcoming of several technological challenges, which includes the development of safe and effective storage solutions. In the recent decades, different hydrogen storage materials (HSM) have been investigated for hydrogen storage in the solid state, such as simple hydrides, borohydrides, metalorganic frameworks (MOFs), alanates, intermetallic alloys, ammonia borane, and carbon-based compounds. Technological advances in HSM can be monitored from the patent document analysis applying bibliometrics coupled with text mining. In this study, the stage of the technology life cycle was evaluated, as well as the most prominent HSM and the role of different countries on this subject. Patent data were recovered from the Derwent Innovations Index database (DII), processed in bibliometric software VantagePoint® and used for the preparation of technical indicators. Patents in HSM decreased after 2007, except in China. The territories with more expressive patenting activity were the US, Japan, China and the European Union. Simple hydrides and borohydrides were the main classes for triadic patents in the US and EU, while Japan had a high participation in solid solution alloys. Despite its high number of patent applications, China has no triadic patents on HSM, raising doubts about the technological value of its domestic patents. The life-cycle assessment seems to show that the current stage is between the first prototype experiments in the market and a more spread use of the technologies; however, continued monitoring on the subject is necessary for a more accurate analysis.